Pengembangan Aplikasi Monitoring Jaringan Berbasis Web di PT Agiva Indonesia Menggunakan Metode Analisis Real Time dan Protocol SNMP - Mardiko Ramadhan; Bobi Agustian (Teknik Informatika Universitas Pamulang, 2025)
This study aims to develop a web-based network monitoring application named SunSets (System Utilization Network Solution and Enhancement Technology Software) as a solution for monitoring local network infrastructure at PT Agiva Indonesia. The system implements near real-time monitoring using the SNMP protocol through periodic polling every one minute, which has been technically proven to consistently detect changes in device conditions. This research adopts a Research and Development (R&D) approach consisting of problem identification, requirements analysis, system design, implementation, and testing stages. Supporting data were collected through interviews and direct observation of the company’s local network infrastructure. Testing was conducted through OrbStack simulation using Linux Ubuntu to replicate the network environment and to evaluate performance parameters such as response time, polling reliability, and user satisfaction level. The results indicate that the application achieves an average response time of 148 ms, detection accuracy of 99.1%, and polling reliability of 98.7%. User evaluation based on a Likert-scale questionnaire shows that the majority of respondents selected strongly agree and agree, indicating that the SunSets application is easy to use and effective. This study demonstrates that near real-time monitoring using the SNMP protocol can improve the reliability and performance of enterprise networks.